Financialization and Innovation Short-termism in OECD Countries - Lee, Young Soo; Kim, Han Sung; Hwan Joo, Seo (Review of Radical Political Economics, 2020)
This study looks at how financialization has changed technology innovation strategy. It is our contention that, as conditions of managerial myopia worsen in line with deepening financialization, economic entities direct technological innovation strategy toward incremental innovation at the expense of radical innovation that involves high-risk and long-term investment. We test this hypothesis on data for thirty-one OECD countries between 1990 and 2006 and use both generalized method of moments estimation and Poisson regression models. We find that, as financialization advanced, the radicalness of technological innovation declined, while the number of patent registrations increased. This finding could be the result of recent trends wherein financialization has led to a rise in corporate funding through financial markets and an increase in the importance of patents, which, in turn, has boosted the motivation of companies to increase their patent registrations quantitatively. On the other hand, the qualitative importance of these patents (radicalness of technological innovation) decreased over the period of study, reflecting growing short-termism in technological innovation strategy.
Keywords: B52; citation; financialization; innovation strategy; O32; patent; radicalness; short-termism